In Praise of Wind Turbines - Welsch, Wolfgang (Scenari, 2023)
Are wind turbines an aesthetic disaster or could they represent aesthetic fortune? Couldn’t we perceive them as a fascinating species newly populating our planet? Wind turbines make it clear that the idyllic nature we love is in fact not pure nature but deeply modified by civilization. Wind turbines are enlightening in revising our accustomed perception of nature.